Strain Diversity of Mycobacterium tuberculosis Isolates from Pulmonary Tuberculosis Patients in Afar Pastoral Region of Ethiopia - Belay, Mulugeta (Hindawi Publishing Corporation, 2014)
Data on genotypic diversity of Mycobacterium tuberculosis complex (MTBC) is important to understand its epidemiology, human adaptation, clinical phenotypes, and drug resistance. This study aimed to characterize MTBC clinical isolates circulating in a predominantly pastoralist area in Ethiopia, a country where tuberculosis is the second leading cause of mortality. Culture of sputum samples collected from a total of 325 pulmonary TB suspects was done to isolate MTBC. Spoligotyping was used to characterize 105 isolates from culture positive slopes and the result was compared with an international database. Forty-four spoligotype patterns were observed to correspond to 35 shared-types (SITs) containing 96 isolates and 9 orphan patterns; 27 SITs containing 83 isolates matched a preexisting shared-type in the database, whereas 8 SITs (n = 13 isolates) were newly created. A total of 19 SITs containing 80 isolates were clustered within this study (overall clustering of 76.19%). Three dominant lineages (T, CAS, and Manu) accounted for 76.19% of the isolates. SIT149/T3-ETH was one of the two most dominant sublineages. Unlike previous reports, we show that Manu lineage strains not only constitute a dominant lineage, but are also associated with HIV infection in Afar region of Ethiopia. The high level of clustering suggests the presence of recent transmission that should be further studied using additional genotyping markers.